KAJIAN ETNOBOTANI TUMBUHAN BERKHASIAT OBAT SUKU TIALO DI DESA TAOPA KECAMATAN TAOPA KABUPATEN PARIGI MOUTONG - Siska Anggraini; Miswan Miswan; Ramadhanil Pitopang (Biocelebes, 2016)
Research on the study of ethnobotany medicinal plants in Tialo tribe in the village of the District Taopa Taopa Moutong Parigi district, Central Sulawesi has been carried out from January to March 2015. This study aimed to obtain information about the species of plants are utilized, plant organs used, the type of disease being treated and how the use of medicinal plants by Tialo tribe in the village of Taopa. This research is a descriptive research through semi-structured interviews with 42 respondents using questionnaire. Based on the obtained results of research conducted as many as 42 species of plants are used as traditional medicine. Part of the plant used, among others, the leaves of 48%, 26% fruit, rhizome 10%, 7% root, stem 2%, 2% interest, and all plant organs 5%. Taopa rural communities utilizing medicinal plants to treat chronic diseases, infectious and noninfectious. How to use it is boiled, pounded, paste, blended and eaten .   Keywords: Ethnobotany, Plant Medicine, Tialo Tribe